TEACHERS' PERCEPTION AND PRACTICE IN IMPLEMENTING TECHNOLOGY-MEDIATED TASK-BASED LANGUAGE TEACHING IN SMP NEGERI 4 SINGARAJA - Rahayu, Ni Made Ririn; Ratminingsih, Ni Made; Eka Wahyuni, Luh Gede (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study explores the perception and practices of English teachers in implementing technology-mediated task-based language teaching. The study adopted a sequential explanatory mix-research design. The data were collected through questionnaires, classroom observation, and interviews. This data was analyzed to identify the gap between theoretical understanding and practical application. the findings reveal that teacher possess a strong understanding of TMTBLT principles and recognize its benefits. However, practical implementation is constrained by external challenges, such as limited access to technology and large class sizes. The teachers frequently utilize tools like PowerPoint and YouTube. Managing collaborative tasks in large classes is often faced with unequal participation. It highlights the difficulty in applying the student-centered method effectively. This found that the successful implementation of TMTBLT requires systemic improvement in infrastructure and targeted professional development. By addressing this limitation, the teacher can align their positive perception with effective classroom practice. The study emphasizes the importance of supporting teachers to fully realize the potential of TMTBLT in creating engaging, collaborative, and meaningful learning experiences for students.